2018
DOI: 10.1080/0886022x.2018.1487856
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes decreases patency of tunneled catheters in hemodialysis patients after first effective thrombolysis with urokinase

Abstract: Introduction: Fibrinolysis is one of the methods extending the use of vascular access in patients with tunneled venous catheters thrombosis. The aim of this study was to assess one-year maintenance of tunneled catheters patency after first effective thrombolysis with urokinase and identify its predictors.Methods: Retrospective analysis included 85 patients (age 69 ± 13 years) with permanent venous catheter thrombosis treated with urokinase at one center in the period 2010–2016. Urokinase was used (depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…A similar study from India reported that during three years period total 45% catheters of which majority were electively removed due to death with functioning catheter, switch to AVF and renal transplant [19]. Increasing age and diabetes were documented as independent factors negatively affecting catheter patency but our data did not suggest any such association [21,33].…”
Section: Discussioncontrasting
confidence: 58%
“…A similar study from India reported that during three years period total 45% catheters of which majority were electively removed due to death with functioning catheter, switch to AVF and renal transplant [19]. Increasing age and diabetes were documented as independent factors negatively affecting catheter patency but our data did not suggest any such association [21,33].…”
Section: Discussioncontrasting
confidence: 58%
“…Hence these studies might not be of much help for long-term medical planning and future resource allocation. Although age, 8,9 diabetes 10,11 and gender 12,13 are well recognized as the risk factors for maturation and function of VA, studies on whether these factors increase the VA associated economic burden are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there were more diabetes mellitus patients at baseline of demographic characteristics in the sodium bicarbonate group compared with the heparin group (66.7% vs 42.6%, P = .01; Table 1 ). Wójtowicz et al 26 showed that diabetes mellitus was one of the poor predictors of catheter survival (HR = 0.31, 95% CI = 0.11-0.92, P = .03) due to its pro-thrombotic state. This could be explained by endothelial injury, hyperfibrinogenemia, and platelet hyperreactivity related to increased glucose levels as well as hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%